FINANCING PROGRAMS: HORIZON 2020 - Cristiana SÎRBU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to present the financing program called Horizon 2020 and the importance of financing programs in agriculture. Agriculture and forestry have always had and maintain an important role for EU’s society. Horizon 2020 has the political backing of Europe’s leaders and the Members of the European Parliament. Horizon 2020 seeks to improve simultaneously the productivity and sustainability of agriculture and forestry while strengthening related food and non-food industries. It also seeks to empower rural communities to boost economic diversification and delivery of ecosystem services.